KOREKSI KESALAHAN EJAAN PADA PENCARIAN ARTIKEL PARIWISATA BERBAHASA INDONESIA MENGGUNAKAN LEVENSHTEIN DISTANCE - Suzanti, Ika Oktavia; Dwi Putra Negara, Yudha; Radiah, Aisyatur; Dwi Cahyani, Andharini; Husni, Husni (Jurnal Simantec, 2024)
The information technology development in current digital era, brings changes and fast and accurate access to information in all aspects of human life, including tourism news as one example. In deciding to go on vacation to a place, tourists need references to tourist attractions, one of which is through online articles. This makes it easier for tourists to find references through tourism news portals using search engines. Spelling correction is the most common way to identify and provide suggestions or ideas for misspelled words in a text. Spelling correction can be used to correct spelling errors from Indonesian queries entered into tourism articles. The Levenshtein Distance method is one method that can be used to correct spelling errors caused by typing errors so that the results given do not match the existing query (keywords). This method works by creating a matrix to measure the amount of difference between two string s. The results of this study indicate that the use of the Levenshtein Distance method in correcting word spelling is very good with a precision value of 1.0 and a recall of 0.89.Keywords: Indonesian language, Spelling Correction, Levenshtein Distance